Are Taiwanese Afraid of Terrorism? The Impacts of Hard and Soft Terrorism on Taiwanese - Tulga, Ahmet Yiğitalp (Global: Jurnal Politik Internasional, 2022)
Technological developments in the last 20 years have affected people's daily lives and caused many innovations. The internet and social media are among the most important developments, and these developments have led to an increase in the speed of news and people's rapid access to information on various topics. However, progress in technology has also affected terrorist organisations. This effect has changed the methods, strategies, and visions of terrorist organisations. With these new methods and strategies, terrorist organisations could negatively affect the psychology of the people who are not directly affected by global terrorism. The best example of this is Taiwan. In this study, I focus on the impact of hard and soft terrorism on the Taiwanese. In this direction, I use the mixed-method approach in this study. I analyse the 7th wave of the World Values Survey with the Ordinary Least Square (OLS) regression method. Qualitative face-to-face interviews with Taiwanese will support the quantitative results.